2022
DOI: 10.3390/antibiotics11020276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bi-Lateral Co-Infections and Antibiotic Resistance Rates among COVID-19 Patients

Abstract: In addition to the pathogenesis of SARS-CoV-2, bacterial co-infection plays an essential role in the incidence and progression of SARS-CoV-2 infections by increasing the severity of infection, as well as increasing disease symptoms, death rate and antimicrobial resistance (AMR). The current study was conducted in a tertiary-care hospital in Lahore, Pakistan, among hospitalized COVID-19 patients to see the prevalence of bacterial co-infections and the AMR rates among different isolated bacteria. Clinical sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…It resulted in 445 million (M) reported cases and 6 M deaths worldwide [ 4 ]. Out of which, cases from Pakistan accounted for 1.15 M and 30,265 deaths [ 5 ]. The high transmissibility and associated mortality rates have raised concerns among clinicians and scientists [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It resulted in 445 million (M) reported cases and 6 M deaths worldwide [ 4 ]. Out of which, cases from Pakistan accounted for 1.15 M and 30,265 deaths [ 5 ]. The high transmissibility and associated mortality rates have raised concerns among clinicians and scientists [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…By the first week of April 2020, more than 890,000 cases and over 45,000 deaths had been reported worldwide. 11 The death toll in India had reached 200, with Maharashtra being the worst affected state in the country. 12 Throughout the lockdown period, the patient inflow in Nair Hospital Dental College was minimal, probably due to stringent travel restrictions and fear of transmission of infection among patients during dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic reports that provide a thorough overview of AMR in the country have not been published yet [ 32 ]. In previous studies, AMR in clinically significant bacteria in Pakistan was discussed; the authors identified the gaps in surveillance and provided references for impending work while also recommending regulations and guidelines for government officials and consumers on evidence-based measures to minimize AMR in Pakistan [ 13 , 24 ]. The exploitation of AI in Pakistan is not common, except in a few healthcare setups.…”
Section: Use Of Artificial Intelligence In Pakistanmentioning
confidence: 99%
“…The Regulation and Coordination Department of the Pakistan Ministry of National Health Services, along with the NIH, pledges to develop a nationwide AMR monitoring system that includes animal, human, and resistance surveillance; creation of federal and provincial AMR labs in at least two provinces; and reduction in infection incidence and prevalence in Pakistan [ 31 ]. They also pledge to finish the project of Tricycle ESBL E. coli and expand the International AMR Monitoring System, as well as share relevant findings globally [ 13 ].…”
Section: Use Of Artificial Intelligence In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation